Berruyer's Bible : public opinion and the politics of enlightenment Catholicism in France - Watkins, Daniel J. (McGill-Queen's studies in the history of religion., 2021)
"The French Jesuit Isaac-Joseph Berruyer's Histoire du peuple de Dieu was an ambitious attempt to connect the ideas of the Enlightenment with the theology of the Catholic Church. A paraphrase of the Bible written in vernacular French, the Histoire promoted progress, the pursuit of happiness, the fundamental goodness of humanity, and the capacity of nature to shape moral human beings. Berruyer aimed to update the Bible for a new age, but his work unleashed a furor that ended with the expulsion of the Jesuits from France. Berruyer's Bible offers a fresh perspective on the history of the Catholic Enlightenment. By exploring the rise and fall of Berruyer's Histoire, Daniel Watkins reveals how Catholic attempts to assimilate Enlightenment ideas caused conflicts within the church and between the church and the French state. Berruyer's Bible flips the traditional narrative of the Enlightenment on its head by showing that the secularization of French society and the political decline of the Cathoblic Church were not due solely to the external assaults of anti-clerical philosophes but also to the internal discord caused by Catholic theologians themselves. Built upon extensive research in archives across Western Europe and the United States, Berruyer's Bible paints a vivid picture of the tumultuous intellectual world of the Catholic Church and the power of radical ideas that shaped the church throughout the Enlightenment, the French Revolution, and beyond."--